Hepatitis E virus genotype 3 in mussels (Mytilus galloprovinciallis), Spain. (September 2016) - Mesquita, João R.; Oliveira, Danielle; Rivadulla, Enrique; Abreu-Silva, Joana; Varela, Miguel F.; Romalde, Jesús L.; Nascimento, Maria S.J.
Abstract: Coastal waters can become contaminated with both human waste from sewage treatment plants and runoff following manure application. Thus, shellfish produced close to land can bioaccumulate enteric viruses of human and animal origin, including zoonotic hepatitis E virus that infect both human and swine. The goal of this study was to evaluate the presence of HEV in shellfish from Galicia (NW Spain), a densely populated region with a strong tradition of swine farming, and one of the most important regions in the world for mussel production. We tested 81 mussel batches by RT-qPCR followed by conventional broad-spectrum nested RT-PCR and phylogenetic analysis. We have obtained 12 positive samples by RT-qPCR (14.81%) with HEV contamination levels ranging from 6.7 × 10 1 to 8.6 × 10 4 RNA copies/g digestive tissue. Phylogenetic analysis based on a 330 nt region of the ORF 1 showed that all sequenced isolates belonged to the zoonotic genotype 3 subgenotype e, being closely related to strains of human and swine origin. Results show that shellfish may be a potential route for HEV transmission to humans. Highlights: Detection of HEV in shellfish harvested areas is described. HEV levels ranged from 6.7 × 10 1 to 8.6 × 10 4 RNA copies/g digestive tissue. All sequenced isolates belonged to the zoonotic genotype 3e. Shellfish constitute a potential route for HEV transmission to humans.